India and the SCO: Cultivating Stronger Ties with the Eurasian Region - M. Singh Roy (Международная аналитика, 2015)
Present paper examines India’s growing interest and role which it seeks to play in this Eurasian organization. India’s economic potential, vast experience and institutional capabilities can add greater value and share best practices in newer areas, the biggest challenge for India would be to adapt to the new geopolitical reality in the region.